2009
DOI: 10.1108/14626000911000956
|View full text |Cite
|
Sign up to set email alerts
|

The dyadic bank‐SME relationship

Abstract: PurposeThis paper aims to emphasise the theory of adaptation in the analysis of banks' ability to meet the needs of their SME customers. This analysis involves examining the interaction process between the two parties, determining how the role of bankers is perceived and studying how banks as organisations function.Design/methodology/approachIn the study a total of 60 interviews are conducted, of which 45 are conducted with SME owners. For this specific study, data drawn from in depth interviews conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The positive impact of social media on local bank performance is statistically significant as well as economically relevant. As discussed in Section 5, two mechanisms may explain the improved performance of local banks active in social media: the development of a business model based on close relationships, and the strengthening of lock-in phenomenon due to increased information asymmetry between relationship lenders and other potential capital providers (Prilmeier, 2017;Rajan, 1992). The lack of a stable and positive impact of social media activity on loan dynamics, we believe, slightly privileges the second explanation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The positive impact of social media on local bank performance is statistically significant as well as economically relevant. As discussed in Section 5, two mechanisms may explain the improved performance of local banks active in social media: the development of a business model based on close relationships, and the strengthening of lock-in phenomenon due to increased information asymmetry between relationship lenders and other potential capital providers (Prilmeier, 2017;Rajan, 1992). The lack of a stable and positive impact of social media activity on loan dynamics, we believe, slightly privileges the second explanation.…”
Section: Discussionmentioning
confidence: 87%
“…Second, social media may help local banks to more efficiently lock-in customers in the existing relationships. It may facilitate the acquisition of soft information and increase the advantage of local banks over other potential lenders, creating a form of information monopoly (Ongena & Smith, 2001;Prilmeier, 2017;Rajan, 1992). Unfortunately, from our data, we cannot differentiate between these two explanations.…”
Section: Social Media Impact On Performancementioning
confidence: 88%
“…The respondents were company managers and cannot provide accurate views of the customers' emotional needs and involvement. Silver and Vegholm (2009) examined the role of customer adaptation in interaction and the bankers' ability to meet the needs of their SME customers. The findings indicated that the adaptation process was affected by lack of communication and contact in the interaction process.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Taking additionally into account that the number of social media users is consistently growing and is expected to exceed 3 billion users by 2021 (eMarketer, 2017), it is not surprising that social media shift to the center of interests of not only entrepreneurs but also researchers. Current empirical evidence related to the impact of social media on economic life concerns mostly: (a) the strengthening of a customer-company relationship and engagement (Mangold & Faulds, 2009;Kaplan & Haenlein, 2010;Bolton, 2011;Tsimonis & Dimitriadis, 2014;Laroche, Habibi, Richard, & Sankaranarayanan, 2012;Lipsman, Mudd, Rich, & Bruich, 2012;Durkin, McGowan, & Murray, 2014), (b) improved efficiency of marketing (Edelman, 2010;Gallaugher & Ransbotham, 2010;Pozza, 2014;Cawsey & Rowley, 2016), or (c) stimulation of brand awareness and loyalty (Silver & Vegholm, 2009;Farshid, Plangger, & Nel, 2011;Laroche, Habibi, & Richard, 2013;Larsson & Vitaoja, 2017). Contributions related to financial aspects of social media adoption are relatively scarce, and concern mostly non-financial companies and links between social media investment and firm value or performance (Plangger, 2012;Paniagua & Sapena, 2014;Kim, Koh, Cha, & Lee 2015a;Kim, Lim, & Brymer, 2015b;Hsu & Lawrance, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Within the first abovementioned literature strand, the authors prove that social media strengthen long-term relationships with clients (Mangold & Faulds, 2009;Kaplan & Haenlein, 2010;Laroche et al, 2012;Lipsman et al, 2012;Durkin et al, 2014), improve efficiency of marketing efforts (Edelman, 2010;Gallaugher & Ransbotham, 2010;Pozza, 2014;Cawsey & Rowley, 2016), generally increase consumer engagement (Bolton, 2011;Tsimonis & Dimitriadis, 2014), and stimulate brand awareness, loyalty, and trust (Silver & Vegholm, 2009;Farshid et al, 2011;Laroche et al, 2013;Larsson & Vitaoja, 2017). As far as the content type of social media activity is concerned, it is shown that the characteristics of Facebook posts such as post type, category, and posting day influence users' interaction in terms of the number of comments and likes, as well as its duration (Cvijikj & Michahelles, 2011).…”
mentioning
confidence: 99%